2018
DOI: 10.1002/2017jc013019
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Redfieldian Dynamics Explain Seasonal pCO2Drawdown in the Gulf of Bothnia

Abstract: High inputs of nutrients and organic matter make coastal seas places of intense air‐sea CO2 exchange. Due to their complexity, the role of coastal seas in the global air‐sea CO2 exchange is, however, still uncertain. Here, we investigate the role of phytoplankton stoichiometric flexibility and extracellular DOC production for the seasonal nutrient and CO2 partial pressure (pCO2) dynamics in the Gulf of Bothnia, Northern Baltic Sea. A 3‐D ocean biogeochemical‐physical model with variable phytoplankton stoichiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 103 publications
0
36
0
Order By: Relevance
“…The pCO 2 was measured during 25 cruises, spanning January to October 2012, with the TransPaper cargo (Fransson et al, 2019). The TransPaper cargo sails from Gothenburg on the Swedish west coast, through the Baltic Proper and northwards through the Bothnian Sea and the Bothnian Bay to the ports of Oulu and Kemi in Finland.…”
Section: Pco 2 Datamentioning
confidence: 99%
“…The pCO 2 was measured during 25 cruises, spanning January to October 2012, with the TransPaper cargo (Fransson et al, 2019). The TransPaper cargo sails from Gothenburg on the Swedish west coast, through the Baltic Proper and northwards through the Bothnian Sea and the Bothnian Bay to the ports of Oulu and Kemi in Finland.…”
Section: Pco 2 Datamentioning
confidence: 99%
“…The third set contains an experiment (1YS), which is similar to the 1Y experiment, but a tDOC dependent light parameterization is used instead of a salinity dependent one, as described in Fransner et al (2018). The aim of 1YS is to investigate the potential indirect effect tDOC could have on the pCO 2 by dampening phytoplankton growth and carbon fixation.…”
Section: Simulationsmentioning
confidence: 99%
“…Additionally, parameterization of nutrient and Chl : C ratios according to, for example, Geider and La Roche () and Macintyre et al () will be considered in future work. It has been shown that models with constant molecular plankton ratios show poorer performance in the northern Baltic Sea (Eilola et al ), while Fransner et al () showed that including non‐Redfieldian dynamics in biogeochemical models may improve the representation of the carbon dynamics in these boreal waters. The contrasting results indicate that more research is needed to fully understand the causes for deviations and to implement new process knowledge in future scenarios.…”
Section: Discussionmentioning
confidence: 99%